2021
DOI: 10.1002/pam.22325
|View full text |Cite
|
Sign up to set email alerts
|

Skipping the Bag: The Intended and Unintended Consequences of Disposable Bag Regulation

Abstract: Regulation of goods associated with negative environmental externalities may decrease consumption of the targeted product, but may be ineffective at reducing the externality itself if close substitutes are left unregulated. We find evidence that plastic bag bans, the most common disposable bag regulation in the U.S., led retailers to circumvent the regulation by providing free thicker plastic bags, which are not covered by the ban. In contrast, a regulation change that replaced the ban with a small tax on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…When Homonoff et al directly compared the environmental costs associated with disposable bag use across the life cycle of the bags (from production to cleanup) during a stand-alone ban in Chicago and during the imposition of a tax on all disposable shopping bags, they found that customers used the life-cycle cost equivalent of over six additional lightweight plastic bags per shopping trip during the ban relative to during the tax. 13 It is important to note that the research we have discussed in this article also indicates that even small taxes on disposable bags can lead to major changes in consumer behavior. Hence, policymakers who want to decrease disposable bag use but worry about the economic burden that fees would place on consumers-especially low-income shoppers-may want to consider a very small tax.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…When Homonoff et al directly compared the environmental costs associated with disposable bag use across the life cycle of the bags (from production to cleanup) during a stand-alone ban in Chicago and during the imposition of a tax on all disposable shopping bags, they found that customers used the life-cycle cost equivalent of over six additional lightweight plastic bags per shopping trip during the ban relative to during the tax. 13 It is important to note that the research we have discussed in this article also indicates that even small taxes on disposable bags can lead to major changes in consumer behavior. Hence, policymakers who want to decrease disposable bag use but worry about the economic burden that fees would place on consumers-especially low-income shoppers-may want to consider a very small tax.…”
Section: Discussionmentioning
confidence: 80%
“…For example, Taylor obtained similar results using scanner data from a large supermarket chain, 18 and Homonoff et al documented a comparable response to a 7-cent tax in Chicago-a 33 percentage point decrease in disposable shopping bag use. 13 Similar evaluations of disposable bag charges have been conducted in several other countries. Using observational customer data, a team of researchers found that the implementation of a 2.5-cent to 4-cent tax on disposable shopping bags in the city of Buenos Aires led to an increase in the proportion of customers using at least one reusable bag relative to the proportion doing so in Greater Buenos Aires (which was not subject to the tax), with the magnitude of the increase similar to that reported in U.S. studies.…”
Section: Policy Recommendationsmentioning
confidence: 89%
See 2 more Smart Citations
“…As of 2019, there were over 400 state and local laws aimed at curbing disposable carryout bag use in the US alone (Zeitlin, 2019). Studies have found plastic carryout bag bans and taxes to be highly effective in altering consumer bag choices at checkout, substantially decreasing the use of disposable carryout bags and increasing the use of reusable carryout bags (Convery et al, 2007;Dikgang et al, 2012;Homonoff, 2018;Homonoff et al, 2021;Taylor & Villas-Boas, 2016b). However, their effectiveness might be reduced if consumers substitute to unregulated jurisdictions and types of businesses.…”
Section: Introductionmentioning
confidence: 99%